STUDI PENELUSURAN LULUSAN PROGRAM STUDI PENDIDIKAN ANAK USIA DINI - Nurbiana Dhieni (Perspektif Ilmu Pendidikan, 2008)
The information about Early Childhood Education alumni and their career’s development can give input to the Head of Department to develop the department. Research findings describe that Early Childhood Education alumni have quite good GPA, generally above 3,00 and the unemployment period of 3 months. Besides, approximately 92% respondents work on the basis of their competencies. Almost all of them work as lecturers and teachers in the fields related to Early Childhood Education.